2012
DOI: 10.1063/1.4718352
|View full text |Cite
|
Sign up to set email alerts
|

Shear-mode magnetostrictive/piezoelectric composite with an enhanced magnetoelectric coefficient

Abstract: ; et al., "Shear-mode magnetostrictive/piezoelectric composite with an enhanced magnetoelectric coefficient," Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Besides normal stress, another vibration mode, shear mode, with high resonant frequency, is also very common and widely utilized in different kinds of piezoelectric sensors. Not surprisingly, it has attracted attention of the researches in ME composites recently [11][12][13][14]. A ME sensor with stretch Terfenol-D and one-side shear PMN-PT was reported with comparable sensitivity, with two PMN-PT layers fabricated in this structure and one PMN-PT layer's shear ME coefficient measured [12].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Besides normal stress, another vibration mode, shear mode, with high resonant frequency, is also very common and widely utilized in different kinds of piezoelectric sensors. Not surprisingly, it has attracted attention of the researches in ME composites recently [11][12][13][14]. A ME sensor with stretch Terfenol-D and one-side shear PMN-PT was reported with comparable sensitivity, with two PMN-PT layers fabricated in this structure and one PMN-PT layer's shear ME coefficient measured [12].…”
mentioning
confidence: 94%
“…Not surprisingly, it has attracted attention of the researches in ME composites recently [11][12][13][14]. A ME sensor with stretch Terfenol-D and one-side shear PMN-PT was reported with comparable sensitivity, with two PMN-PT layers fabricated in this structure and one PMN-PT layer's shear ME coefficient measured [12]. Based on this study, a ME laminated sensor with two magnetostrictive layers and one piezoelectric layer both operated in shear mode was investigated which enhanced the field sensitivity remarkably [14].…”
mentioning
confidence: 99%
“…The ME effect is defined as a variation of dielectric polarization in a material when subjected to an applied magnetic field 6. Previous reports indicated that the linear response of the ME sensor was the best 7, 8. However, the linear response of ME composites is sensitive to the intrinsic and extrinsic noises including the vibrational noise introduced via the piezoelectric effect and the intrinsic noise, such as Johnson noise, 1/ f noise in the resistors and semiconductors of the detection circuit 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al introduced a third phase as a clamping substrate, other than the magnetostrictive phase and piezoelectric phase. 28 The piezoelectric layers deform in the shear-mode rather than the longitudinal mode, and a ME coefficient of about 7.5 V/cm Oe was observed. A composite of multilayers of magnetostrictive substance Metglas and piezoelectric substance PMN-PT fibers was reported to exhibit a ME coefficient of 52 V/cm Oe.…”
mentioning
confidence: 98%